Qiraah fi ba'd al mudhakkirat wa al rasail al shakhsiyyah li al shaykh al Muarrikh wa al nasabah Ibrahim Ibn 'Isa - Ahmad Ibn 'Abdulaziz Ibn Muhammad al Bassam (Darah al Malik Abdulaziz, 2006)
sgh.1/sgh.c1